The Melancholy Monument of the Left - Rethmann, Petra (Anthropologica, 2022)
From November 2017 to April 2018, in Mexico City’s Museo Universitario Arte Contemporaneo, the Russian artistic-activist collective chto delat (what should be done?) exhibited a number of monuments in memory of the Russian revolution. In centring on three monuments, in this article I consider the ability of the collective’s monuments to inspire political mediations on historical potential embedded in revolutionary pasts. I argue that melancholia does not inevitably mark historical fixity or unaccomplished mourning, but rather a temporal openness to mnemonic productivity and solidarity. It is in this sense that melancholia does not index a pathological response to loss, but a political alternative to normative mourning. In recuperating melancholia as a potentially productive and critical relation to the past, chto delat reframes accusations of left-wing melancholia as being “stuck in the past” as an opening to consider alternatives to what is now.